CuO–NiO/Co3O4 hybrid nanoplates as highly active catalyst for ammonia borane hydrolysis. (18th March 2020) - Liao, Jinyun; Feng, Yufa; Lin, Weimin; Su, Xinlong; Ji, Shan; Li, Liling; Zhang, Wanling; Pollet, Bruno G.; Li, Hao
Abstract: Dehydrogenation of hydrogen-rich chemicals, such as ammonia borane (AB), is a promising way to produce hydrogen for mobile fuel cell power systems. However, the practical application has been impeded due to the high cost and scarcity of the catalysts. Herein, a low-cost and high-performing core-shell structured CuO–NiO/Co3 O4 hybrid nanoplate catalytic material has been developed for the hydrolysis of AB. The obtained hybrid catalyst exhibits a high catalytic activity towards the hydrolysis of AB with a turnover frequency (TOF) of 79.1 molH2 mol cat −1 min −1 . The apparent activation energy of AB hydrolysis on CuO–NiO/Co3 O4 is calculated to be 23.7 kJ.mol −1 . The synergistic effect between CuO–NiO and Co3 O4 plays an important role in the improvement of the catalytic performance. The development of this high-performing and low-cost CuO–NiO/Co3 O4 hybrid catalytic material can make practical applications of AB hydrolysis at large-scale possible. Graphical abstract: Image 1 Highlights: CuO–NiO/Co3 O4 nanoplates are developed for the hydrolysis of ammonia borane. CuO–NiO/Co3 O4 delivers a turnover frequency of 79.1 molH2 mol cat −1 min −1 . Synergistic effect between CuO–NiO and Co3 O4 played an important role in enhancing catalytic performance.